AN OVERVIEW OF CHALLENGES, IMPORTANCE AND EVALUATION OF PHARMAECONOMICS: ROLE OF PHARMACIST’S IN HEALTH CARE SYSTEM - Shubhangi Gupta; Shiwangi Periwal; Bankim Chandra Nandy; Beduin Mahanti (Journal of Biomedical and Pharmaceutical Research, 2020)
The main goal of the pharmacoeconomics is to addresses whether an additional gain from a medical intervention is worth paying extra cost based on three aspects of health outcomes: Economic, Clinical and Humanistic outcome known as ECHO Model. Bys perceptive the principles, methods, and application of pharmacoeconomics, pharmacists will be prepared to make better, more-informed decisions regarding the use of pharmaceutical products and services, that is, decisions that ultimately represent the best interests of the patient, the health care system, and society. Pharmacoeconomics can be applied to any therapeutic area like hospital pharmacy, using a variety of application strategies. As the healthcare sector is progressing day by day the need to develop Pharmacoeconomics area is must. Healthcare sector is not just a small area but it became an industry now. It has more dimensions to explore. So, main goal of this article was to explain it with in a cumulative way by mentioning two examples- where the first one is direct cost that outlays money and then is indirect cost for the productivity effect. Patients also get benefit out of Pharmacoeconomics findings. Pharmacoeconomics research should be strongly supported in a country like India where majority of health care spending is done by the patient’s themselves. Keywords: Pharmacoeconomics, ECHO Model, Pharmacist, Pharmacoeconomic evaluation, Healthcare Sector, Pharmaceutical Policy, Drug Commercialization, Cost Utility Analysis, Cost Benefit Analysis, Cost of illness Analysis, Cost Minimization Analysis.